Glial cell activity is maintained during prolonged inflammatory challenge in rats - Borges, B.C. (Sociedade Brasileira de Medicina Tropical, 2012)
We evaluated the expression of glial fibrillary acidic protein (GFAP), glutamine synthetase (GS), ionized calcium binding adaptor protein-1 (Iba-1), and ferritin in rats after single or repeated lipopolysaccharide (LPS) treatment, which is known to induce endotoxin tolerance and glial activation. Male Wistar rats (200-250 g) received ip injections of LPS (100 µg/kg) or saline for 6 days: 6 saline (N = 5), 5 saline + 1 LPS (N = 6) and 6 LPS (N = 6). After the sixth injection, the rats were perfused and the brains were collected for immunohistochemistry. After a single LPS dose, the number of GFAP-positive cells increased in the hypothalamic arcuate nucleus (ARC; 1 LPS: 35.6 ± 1.4 vs control: 23.1 ± 2.5) and hippocampus (1 LPS: 165.0 ± 3.0 vs control: 137.5 ± 2.5), and interestingly, 6 LPS injections further increased GFAP expression in these regions (ARC = 52.5 ± 4.3; hippocampus = 182.2 ± 4.1). We found a higher GS expression only in the hippocampus of the 6 LPS injections group (56.6 ± 0.8 vs 46.7 ± 1.9). Ferritin-positive cells increased similarly in the hippocampus of rats treated with a single (49.2 ± 1.7 vs 28.1 ± 1.9) or repeated (47.6 ± 1.1 vs 28.1 ± 1.9) LPS dose. Single LPS enhanced Iba-1 in the paraventricular nucleus (PVN: 92.8 ± 4.1 vs 65.2 ± 2.2) and hippocampus (99.4 ± 4.4 vs 73.8 ± 2.1), but had no effect in the retrochiasmatic nucleus (RCA) and ARC. Interestingly, 6 LPS increased the Iba-1 expression in these hypothalamic and hippocampal regions (RCA: 57.8 ± 4.6 vs 36.6 ± 2.2; ARC: 62.4 ± 6.0 vs 37.0 ± 2.2; PVN: 100.7 ± 4.4 vs 65.2 ± 2.2; hippocampus: 123.0 ± 3.8 vs 73.8 ± 2.1). The results suggest that repeated LPS treatment stimulates the expression of glial activation markers, protecting neuronal activity during prolonged inflammatory challenges.